Tackling in Super 15 Rugby 2011 - van Rooyen, M. (World Congress of Performance Analysis of Sport IX, 2012)
In Rugby matches players are frequently exposed to multiple physical contacts and tackles and as a result good defensive and tackling skills are required (Gabbett & Kelly 2007). Success in rugby has also been shown to be linked with tackle frequency and tackling proficiency (Ortega et al., 2009, van den Berg & Malan, 2010, van Rooyen et al., 2008 and Vaz et al., 2011). Data for this comparative study were collected from statistics supplied by Verusco Sport`s Advanced Rugby Analysis System during the 2011 Super 15 rugby competition. The data collected were the number of points conceded; points difference; number of tackles `made` and `missed`. There were an average of 139 (± 34 SD) tackles `made` and 18 `missed` tackles (± 7 SD) per team in a match. The data was combined into Forwards (n = 8) and Backs (n = 7) it was discovered that Forwards contributed 64.4 % ± 6.1 SD and the Backs only 35.6 % ± 6.1 SD (P < 0.05). There was a 1.2 times greater probability of a Forward successfully completing a tackle than would occur by chance and a 1.8 times greater probability a Forward would successfully execute a tackle than a Back. The `missed` tackle data was more equally distributed (Forwards 53.2 % ± 13.2 SD vs. Backs 46.7 % ± 13.4 SD) (P > 0.05). The contribution of the Back Row Forwards to the final tackle count was significantly higher than that of the Scrumhalf and Fly half, Centre and Wings and Fullback groups (P < 0.05) for tackles `made`. The Props & Hookers group contributed more than the Wings and Fullback for tackles `made` (P < 0.05). There were no significant positional differences across the groups for tackles `missed` (P > 0.05). Examination of the data by final log placing shows that 60 % of matches played by teams in the top 6 were won with fewer `missed` compared with only 41 % by the remaining 9 teams. The percentage of `missed` tackles when expressed by positional group did vary significantly between winning and losing teams. Forwards from winning teams `missed` fewer tackles (52.6 % vs. 53.6 % for winning and losing respectively) and the Backs `missed` more tackles (47.0 % winning vs. 46.3 % losing). These data indicated that the percentage of `missed` tackles a team made had an influence on the final result of the game and thus the final log position at the end of the conference stage of the tournament. In addition there were fluctuations in the percentage contribution that the Forwards and the Backs made towards the final team`s percentage `missed` tackles and this also affected the outcome of the match.